Washing Bacteria by Centrifugation Through a Water-Immiscible Layer of Silicones - Hurwitz, Charles (1965)
Hurwitz, Charles (Veterans Administration Hospital, Albany, N.Y.), Catherine B. Braun, and Richard A. Peabody. Washing bacteria by centrifugation through a water-immiscible layer of silicones. J. Bacteriol. 90:1692–1695. 1965.—A method is described which enables the separation of cells from aqueous suspension without altering the internal aqueous environment of the cells. The method consists of centrifuging the cells from the aqueous environment through a more dense, immiscible solvent consisting of a mixture of two silicones. A thin film of the aqueous environment equal to 7 × 10(−13) ml per cell remains with the bacteria during the separation procedure. The method by which this volume was determined is described. The procedure itself has no measurable effect on viability or permeability of the cells and permits recovery of about 90% of the cells from the aqueous environment. With this method, it has been found that the intracellular water volume of Escherichia coli ML 35 accessible to sucrose or inositol is 1.96 × 10(−12) ml ± 6%, or 85% of the total volume of the cell determined by visual measurement.